Evaluation of a high-speed but low-throughput RT-qPCR system for detection of SARS-CoV-2. Issue 4 (August 2020) - Sakai, J.; Tarumoto, N.; Orihara, Y.; Kawamura, R.; Kodana, M.; Matsuzaki, N.; Matsumura, R.; Ogane, K.; Kawamura, T.; Takeuchi, S.; Imai, K.; Murakami, T.; et al.
Summary: With the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), a high-speed and convenient detection technology should be at the forefront of medical care worldwide. This study evaluated the usefulness of GeneSoC, a compact, high-speed reciprocal flow quantitative reverse transcription polymerase chain reaction system, for the detection of SARS-CoV-2. The results support the use of this system for the rapid identification of SARS-CoV-2. This approach can contribute to the strategic selection of initial management strategies for patients with COVID-19.